(untitled) (Research, Society and Development, 2021)
The objective of this retrospective, observational study was to describe the oral lesions diagnosed in older patients through histopathological reports from the oral pathology service of a private university in Rio de Janeiro over a 19 year period (1999-2017) and to call attention to the oral health of the elderly. Information was collected and analyzed from 713 medical records of patients aged ≥ 60 years old. The data collected included the patient’s age, gender and the type and location of the injury. The mean age of the patients was 68.1 years old, with a higher prevalence of lesions in the 60 to 74 age group. The results showed that three of the four most common oral lesions were more frequent in women and only one (oral squamous cell carcinoma) was more common in men. The 4 most common injuries were: fibrous inflammatory hyperplasia (187; 26.2%), oral squamous cell carcinoma (78; 10.9%), leukoplakia (40; 5.6%) and oral lichen planus (36; 5.0%). These lesions were distributed mainly in the alveolar edge (71; 20.8%) followed by tongue (57; 16.7%), bottom of the vestibule (55; 16.1%), and buccal mucosa (44; 12.9%). The results obtained should be used to alert health professionals, especially dentists, so that early diagnoses of such lesions can be made and thus contribute to improving the quality of care for the elderly.